Long‐term outcome with neoadjuvant electrochemotherapy and sliding canthoplasty in a cat with locally advanced squamous cell carcinoma of the lower and third eyelid. Issue 1 (3rd November 2022) - Ferro, Livia; Rigon, Niccolò; Ciccarelli, Stefano; Barachetti, Laura; Leo, Chiara
Abstract: A 10‐year‐old, female, spayed cat was referred with a lower eyelid mass lesion of the right eye. Fine‐needle aspiration cytology and histopathology revealed a locally advanced squamous cell carcinoma. The cat was treated with three sessions of neoadjuvant electrochemotherapy, which was associated with a good response. After electrochemotherapy treatment, a sliding canthoplasty was performed to reconstruct the eyelid margin. Histology of excised tissue during surgery, post‐electrochemotherapy, demonstrated a lack of neoplastic cells. The patient was still in complete remission 22 months after diagnosis. All treatments were well tolerated, with mild‐to‐moderate and self‐limiting local toxicities, allowing normal eyelid function and preservation of sight. This multi‐modal approach resulted in a long‐term local control. This case report highlights the potential benefit of electrochemotherapy in the neoadjuvant setting, enabling surgical removal and long‐term local tumour control.